The Influence of Office Layout on Employee Job Satisfaction in Companies - Aria Mulyapradana; Aria Elshifa; Ary Dwi Anjarini; Bunga Lestari; Nafiatul Manahilhakim (Penerbit Goodwood, 2026)
Purpose: The purpose of this study is to determine the influence of office space on employee job satisfaction in companies within Pekalongan Regency. Research Methodology: This study employed a quantitative research approach, utilizing various data processing methods including instrument tests, classical assumption tests, simple linear regression, and hypothesis tests. These tests were used to assess whether the office layout has a significant impact on employee job satisfaction. Results: The study found that office layout significantly affects employee job satisfaction. The significance value was found to be 0.006, which is less than 0.05, indicating that there is a significant relationship. The t-value calculated was 2.910, which is greater than the t-table value of 1.692, thus confirming that the Ha hypothesis (alternative hypothesis) is accepted, meaning that office layout does indeed have an impact on job satisfaction, as r-table (0.334) was smaller than the calculated t-value. Conclusions: The study concludes that office layout plays a significant role in influencing employee job satisfaction. The better the arrangement of office space, the higher the likelihood of improved job satisfaction among employees. Limitations: The study's limitations include a limited number of respondents, which may have affected the generalizability of the results. Future studies could address these limitations by involving a larger sample and exploring additional variables that were not covered in this study. Contributions: This research contributes by offering insights into the relationship between office space design and employee job satisfaction, providing solutions for companies seeking to improve work environments and enhance employee satisfaction.